Efficiency of heavy metal adsorption by entrapped Saccharomyces cerevisiae on coconut fibers in upflow anaerobic filter system - Narong, Pakawadee; Petsom, Jirapa; Rattanaponglayka, Kannika (Engineering and Applied Science Research, 2013)
<span style="line-height: 115%; font-family: "AngsanaUPC","serif"; font-size: 16pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;">Treatment of water which is contaminated with high concentration of zinc, one of heavy metals, can be removed by physical methods eg. adsorbed on coconut fibers, peanut skins or sand beds etc. In this study Saccharomyces cerevisiae entrapped on coconut fibers were used for removing zinc in 2 sets of up flow anaerobic fibers system. The flow rate were fixed at 10 l/day and operated for 7 days in each sets. The initial concentration of zinc in the first and second sets were 20 ppm and 50 ppm respectively. The results indicated that when only the coconut fibers were used, the efficiency of zinc adsorption in the first and second sets were 31.57% and 24.11% respectively. On the other hand, 38.14% and 31.89% of zinc were removed when entrapped S. cerevisiae on coconut fibers. The efficiency of system was improved by adding the medium for S. cerevisiae growth into contaminated water. It was found that 49.33% of zinc were removed by this system.